Sistem Pencarian Similaritas Judul Tugas Akhir Menggunakan Metode TF-IDF - Amrulloh, Arif; Adam, Ipam Fuaddina (Fakultas Sains dan Teknologi, Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The final project is a compulsory subject that must be completed by students to get a degree according to the level of higher education taken. Often students or final project supervisors find it difficult to find out whether the title of the proposed final project has been researched before or not. To avoid the title of the final project being the same as the research that has been done previously, a solution is needed, a system for finding the similarity of the title of the final project can be used as a solution to this problem. Many methods can be used for the problem of finding similarity or similarity of data. One method that is often used is TF-IDF which works by calculating the weights. In this research, a system for finding the similarity of the title of the final project will be built by applying the TF-IDF method. The results of the TF-IDF trial with a final project title of 384 data found that the final project title had similarities based on keywords as many as 99 data. The use of the TF-IDF method can be used as a solution for lecturers and students in determining the title of the final project.